Keputusan Pembelian Smartphone Yang Dipengaruhi Oleh Harga Dan Kualitas Produk - Maulidina; Yosafat Vitorio Simanjuntak (Cattleya Darmaya Fortuna, 2023)
It cannot be denied, the development of world technology is currently very rapid, especially the development of smartphones. Smartphones have become one of the important needs for the community, because with the existence of smartphones, people can be assisted in various activities and their daily activities. One of the well-known smartphone companies, namely Xiaomi Inc., with its product, Xiaomi. There are several reasons why people decide to buy Xiaomi, because they are influenced by competitive prices with guaranteed product quality. This study aims to determine the effect of price and product quality on purchasing decisions for Xiaomi brand smartphones in Medan Marelan sub-district. This study used a quantitative approach with data collection methods through questionnaires via G-form, which were distributed to 96 respondents using a purposive sampling technique. Testing the data in this study uses the Validity Test, Reliability Test, Multiple Linear Regression Test, T Test, F Test, and Coefficient of Determination Test. The variables in this study consist of Price (X1), Product Quality (X2) and Purchase Decision (Y). From the test results, it is obtained that the price variable (X1) and product quality variable (X2) have a positive influence on purchasing decisions (Y), with the multiple linear regression test equation Y = 5.236 + 0.084 X1 + 0.272 X2.